The Issues of Literary Relationships and Effects in the Works of Ed. Jrbashyan - JANPOLADYAN, MAGDA (Bulletin of Yerevan University B: Philology, 2021)
The article covers and values the works of academician Jrbashyan related to the issues of Armenian literature in the context of literary effects and relationships. Those issues have always been on the focus of the scientist’s intent attention. Several articles are chosen and analyzed from the various works dedicated to the mentioned issues, as well as the monograph named “Pushkin and Armenian poets”. The questionings on various problems, discoveries on the base of factual material, as well as the thoroughness of conclusions visually prove Ed. Jrbashyan’s solid investment in the research sphere of Armenian literary relationships and effects.
Keywords: academician Jrbashyan, literary ties, many-sided approach, translations, versification, considerable contribution